USA Track & Field (USATF) (2008)
USA Track & Field (USATF) is the National Governing Body for track and field, long-distance running and race walking in the United States. USATF encompasses the world's oldest organized sports, the most-watched events of Olympic broadcasts, the #1 high school and junior high school participatory sport and more than 30 million adult runners in the United States.